Adsorption Study of Diclofenac Potassium on Mint in Aqueous Solutions According to the Freundlich and Langmuir Equations - Mohammed Abdullah Ahmed (Journal of Global Pharma Technology, 2019)
Diclofenac NSAIDs is one of the most commonly prescribed pharmaceutical however its removal from wastewater is only 21-40% which explains their presence in surface water, groundwater and even in drinking water of different countries. This causes environmental and Eco toxic issues, in this context many methods have been proposed for its removal from wastewater. We are proposing a new method for the removal of diclofenac by using adsorption method and using mint as an adsorbing agent this proposes a useful and Eco friendly technique that might be implacable on a large scale in the future.Keywords: Adsorption, Diclofenac, mint.